Herbal sensitivity of Pseudomonas bacteria isolated from cultured tilapia with useful applications in vaccine preparation. - Sulaiman, Siti Fatimah; Mohd Salim, Khairul Afizi; Shamsudin, Mariana Nor; Abdelhadi, Yasser Mohamed (Academic Journals Inc, 2013)
The antibacterial activity of certain commercial antibiotics and common herbs was evaluated against pathogenic Pseudomonas fluorescens, Pseudomonas putida and Pseudomonas aeruginosa isolated from Malaysian and Egyptian cultured fish, mainly tilapia. A suspension of freshly cultured isolates was prepared (with 0.5 OD) and 100 μL of this suspension was spread over the Muller’s Hinton agar plates. The antibiotic discs were inoculated on each cultured plate while the herbal extracts were soaked on Whatman filter paper (20 μL each) that have been cut into discs and later inserted on to bacteria-cultured plates to screen their sensitivity to both antibiotics and herbs. Double-fold dilution was used to determine the Minimal Inhibitory Concentration (MIC) for the effective herbs at 100, 50, 25, 12.5 and 6.25%. Results revealed high resistance of the tested bacteria against most of the screened antibiotics except Ciprofloxacin. With regard to herbal sensitivity, only Origanum vulgare showed effectiveness and inhibition zone against all isolates. The MIC ranged from 15-40% for both Egyptian and Malaysian isolates. Thus, Origanum vulgare is recommended as a feed additive for cultured fish and can also be applied for inactivated and live-attenuated Pseudomonas vaccines’ preparation.